Role of the CHADS-VASc score in predicting hospital stay and 90-day readmission among patients with atrial fibrillation in Syria - Ibrahim Antoun; Alamer Alkhayer; Alkassem Alkhayer; Yaman Mahfoud; Ahmed Kotb; Riyaz Somani; G André Ng; Mustafa Zakkar (Journal of International Medical Research)
Objectives We assessed the CHA 2 DS 2 -VASc score for predicting hospital readmission risk and length of stay (LOS) in patients admitted with primary atrial fibrillation (AF). Methods This retrospective cohort study included patients with index admission for AF to Latakia’s tertiary center (May 2021–November 2023). Patients were followed 90 days to assess readmission. CHA 2 DS 2 -VASc was correlated with 90-day readmission, inpatient all-cause mortality, and LOS during index admission. Results In total, 717 patients were included; 320 (45%) were readmitted to the hospital within 90 days (58% men, 65% aged <65 years). Inpatient mortality was 4%; the median LOS was 2 days. There was an increase in the incident rate ratio (IRR) of LOS starting from a CHA 2 DS 2 -VASc of 2 (IRR: 2, 95% confidence interval [CI]: 1.7–2.2) to a score of >6 (IRR: 5, 95% CI: 1.8–10.7), compared with a score of 0. There was an incremental increase in the hazard ratio (HR) of readmission from a score of 1 (HR: 2.3, 95% CI: 1.3–4.1) to a score of >6 (HR: 41, 95% CI: 31–72) compared with a CHA 2 DS 2 -VASc of 0. Conclusion CHA 2 DS 2 -VASc could predict 90-day hospital readmission and LOS during the index admission in patients admitted with primary AF.